(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Stroke in childhood is serious disorder about which little is published. Objective:To determine demographic and presenting features of children with stroke. Methods:A cross sectional study was conducted on cases of pediatric stroke admitted to Children Welfare Teaching Hospital during May 2008-August 2011. Cases classified radiologically into ischemic and hemorrhagic types. Basic data and clinical presentation were gathered. Results:Sixty nine children (49 boys, 20 girls), aged 1 month-14 years were enrolled. Annual hospital admission rate was 54.2 /100000; boys:girls ratio was 2.5:1, girls were younger than boys. Ischemic stroke was found in 58% of cases. Patients with hemorrhagic stroke were younger than those with ischemic type. Those aged